표고균사로 발효한 한방 펫 푸드 소재의 유용성분 - 김경제; 진성우; 고영우; 임승빈; 하늘이; 정희경; 정상욱; 이동현; 김동욱; 윤경원; 서경순; Kyung-Je Kim; et al. (Journal of mushrooms, 2025)
We developed pet food ingredients for dogs by fermenting oats soaked in herbal extracts of Dendropanax morbifera and Eriobotrya japonica using Lentinula edodes KCTC 18874P mycelium. The resulting materials were analyzed for β-glucan, total polyphenol, essential amino acids, vitamins B1 and B2, calcium (Ca), phosphorus (P), and heavy metals to confirm their beneficial components and safety during consumption. The content of (1-3),(1-4)-β-glucan ranged from 1.08 to 1.78%, with the highest content (1.51%) found in fermented D. morbifera and E. japonica using L. edodes mycelium (FMEJDMOLEM). The (1-3),(1-6)-β-glucan content ranged from 44.14% to 50.13%, with FMEJDMOLEM showing the highest content at 50.13%. The total polyphenol content was highest in FMEJDMOLEM, followed by fermented D. morbifera using L. edodes mycelium (FDMOLEM) and fermented E. japonica using L. edodes mycelium (FEJOLEM). Vitamin B1 content was significantly higher in FMEJDMOLEM, followed by FEJOLEM. FMEJDMOLEM also had the highest vitamin B2 content. The total essential amino acid content was the highest in FMEJDMOLEM, followed by FDMOLEM. FEJOLEM had the highest calcium content. The calcium-tophosphorus ratio in all the samples was below 1:0.8, meeting the standards set by the American Feed Association. Heavy metal analysis confirmed that lead and cadmium, which are hazardous to the health of dogs, were not detected in any of the samples. This study demonstrated the development of pet food materials with high levels of beneficial ingredients, such as β-glucan, appropriate calcium and phosphorus ratios, and no detectable heavy metals, ensuring both usefulness and safety. Our future research will focus on developing dog pet food using these materials, and conducting physiological activity studies to complete the development of scientific dog pet food.